(untitled) (Social Science Review, 2026)
This study explores how gender norms and roles influence the design of humanoid robots (HRs) from the perspectives of inventors and users. HR designs reflect human behaviour, attitudes, and attributes in the technological domain, highlighting how socialization shapes everyday interactions with robots and the roles they play. The gender-biased socialization process and patriarchal structural learning mechanisms encourage men and women to perform gendered roles. The dominance of patriarchal ideals among the designers – mostly men – reinforces the stereotyped ideas fostering gendered behaviour and features of the robots. Based on the voice, appearance, and attributes, users identify robots with masculine or feminine identity, preferring female robots to do care work and male robots to do communal work, which perpetuates the gender binaries. This paper is based on a secondary literature review, and the analysis reveals how socio-cultural norms shape the design and use of HRs, calling for a shift in the ideology of gendering robots to promote gender-neutral technological innovation. Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025, pp. 85-100